Blue carbon stock of the seagrass meadows of Gulf of Mannar and Palk Bay off Coromandel Coast, south India - Kaladharan, P.; Zacharia, P. U.; Thirumalaiselvan, S.; Anasukoya, A.; Ratheesh, Lavanya; Batcha, S. M. Sikkander (Indian Journal of Fisheries, 2020)
Blue carbon stock of the seagrass meadows of Gulf of Mannar and Palk Bay, off Coromandel Coast, south India, were computed from the organic carbon content and dry bulk densities of sediment core taken from the seagrass meadows of these two ecosystems. The Gulf of Mannar (GoM) and Palk Bay (PB) harbour 13 seagrass species dominated by Cymodocea serrulata and Syringodium isoetifolium. The soil carbon density of both GoM and PB were higher in subsurface cores. The blue carbon stock of seagrass meadows of the GoM was estimated as 0.001782 Tg and that of PB as 0.043996 Tg. The estimated value of blue carbon stored in seagrass meadows of GoM was 17820 US$ and that of PB was 43,99,682 US$. The results of this study are discussed in the light of climate change mitigation, emphasising the need to conserve these underwater meadows.Keywords: Blue carbon sink, Climate change, Coromandel Coast, Organic carbon, Seagrass meadows